Synthesis And Characterisation Of Calcium Phosphate Nanoshells Using DOPA and DPPA Liposome Templates - Yeo, Chiew Hwee (2012)
Calcium phosphates (CaPs) are very useful biomaterials in bone tissue engineering due to their excellent biological properties. The major difficulties facing in most of the synthesising methods are the size and the shape-controlling of CaP particles. Therefore, the aim of this project is to synthesise CaP nanoshells by using liposomes as template in order to control the particle size and the shape of the CaP particles. The effectiveness of liposomes (1, 2 dioleoyl-sn-glycero-3-phosphate (sodium salt) (DOPA) and 1, 2-dipalmitoyl-sn-glycero-3-phosphate (sodium salt) (DPPA)) as template were firstly investigated in this project. The results showed that both liposomes formed spherical structures of unilamellar liposomes, in which fulfil the morphology and the size requirement of templates of CaP nanoshells by using suitable preparation method. The effect of concentrations of sodium hydroxide (NaOH) (0.025 M, 0.050 M, 0.075 M, 0.100 M or 0.125 M) and calcium ions (Ca2+) (0.050 M, 0.100 M, 0.150 M or 0.200 M) to the properties of CaP nanoshells prepared using DOPA and DPPA liposome templates were then studied. NaOH plays the role as a base solution to increase the pH, and thus, control the supersaturation of the mixture of CaP nanoshells. In addition, Ca2+ is another main parameter to influence the electrostatic localisation with liposome template and the growth of the CaPs on the liposome template.